(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2025)
The paper aims to reconstruct the procedures of the scrutiny of the laws (a vital part of the ‘evolving law reform’) in late 5th century BCE Athens, approaching them from a broader legal-cultural perspective that highlights the anagrapheis tōn nomōn’s vital role in revealing features of Athenian legal culture. I argue that the anagrapheis were neither mere transcribers of the laws nor officials vested with extensive legislative authority. Instead, their significance lay in the logistical challenges of finding, identifying and collecting laws during the preparatory step, before submission to the Ekklēsia for final approval. The Anagrapheis’ works underscore not their individual relevance per se, but rather the broader complexity, flexibility, and importance of legal scrutiny itself for late 5th century Athens. Thus, contextualising their role within the ‘evolving law reform’ illuminates multiple aspects of Athenian legal culture – ranging from ways of legal thinking, to social attitudes toward legislation, as well as the materiality of laws and the logistical complexities of legal inquiries, such as the establishment of archives, or the ways of publishing laws. After briefly presenting the sources (II), and outlining Nicomachus’ trial (III), I analyse the evidence to highlight key features of legal scrutiny, focusing on the anagrapheis’ vital role (IV), and conclude each subsection by considering what this reveals about Athenian legal culture (IV). A broader examination of the legal scrutiny procedures, law reform complexities, and their connections to legal culture is presented in the final sections (V–VI).